2022
DOI: 10.1021/acscatal.2c04795
|View full text |Cite
|
Sign up to set email alerts
|

ALD-Deposited NiO Approaches the Performance of Platinum as a Hydrogen Evolution Cocatalyst on Carbon Nitride

Abstract: The photocatalytic hydrogen evolution reaction is one of the most promising approaches to utilize solar energy and produce hydrogen as an alternative energy source to traditional fossil fuels. In this work, we focused on further exploring the cocatalyst potential of the transition metal nickel and prepared nickel oxide/ carbon nitride (NiO/CN x ) heterojunctions through thermal polymerization as well as plasma-enhanced atomic layer deposition (PEALD). The optimal NiO loading thickness on the surface of the CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…We first attempted to prepare CN x /FTO electrodes following the procedure in our previous work . The FTO glass was dipped in saturated thiourea solution to crystallize the CN x precursor on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first attempted to prepare CN x /FTO electrodes following the procedure in our previous work . The FTO glass was dipped in saturated thiourea solution to crystallize the CN x precursor on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…We first attempted to prepare CN x /FTO electrodes following the procedure in our previous work. 25 The FTO glass was dipped in saturated thiourea solution to crystallize the CN x precursor on the surface. Thiourea was chosen as the CN x precursor since it is reported that sulfur atoms could work as the molten mediator to initialize the growth of the CN x on the FTO glass.…”
Section: ■ Introductionmentioning
confidence: 99%
“…ALD, as a state-of-the-art technology, can achieve uniform deposition on complex 3D substrates with conformal morphology, which has broad application prospects in the energy field. For example, ALD TiO 2 or NiO on g-C 3 N 4 for photocatalytic hydrogen production, [40,41] as well as ALD TiO 2 thin films, can protect silicon-based hybrid photoelectrodes for photoelectrochemical hydrogen production. [42] In terms of hydrogen sensing, ALD can coat oxide sensing layers and prepare hydrogen sensing optical fibers.…”
Section: Ald In Energymentioning
confidence: 99%